2019
DOI: 10.1002/asia.201900364
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Azide‐Functionalized Ionic Liquids as Attractive Hypergolic Fuels

Abstract: Hypergolic ionic liquids (ILs) have shown a great promise as viable replacements for toxic and volatile hydrazine derivatives used as propellant fuels, and hence, have attracted increasing interest over the last decade. To take advantage of the reactivity and high energy density of the azido group, a family of low‐cost and easily prepared azide‐functionalized cation‐based ILs, including fuel‐rich anions, such as nitrate, dicyanamide, and nitrocyanamide anions, were synthesized and characterized. All the dicyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Considerable efforts have been devoted to the development of new high-performance HILs with heterocyclic and open-chain cations in combination with highly reactive anions. To date, a large number of room-temperature HILs have been developed as promising hypergolic fuels, which are considered as potential green replacements for hydrazine-based fuels in future chemical propellants.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to the development of new high-performance HILs with heterocyclic and open-chain cations in combination with highly reactive anions. To date, a large number of room-temperature HILs have been developed as promising hypergolic fuels, which are considered as potential green replacements for hydrazine-based fuels in future chemical propellants.…”
Section: Introductionmentioning
confidence: 99%
“…Several salts of nitrocyanamide including alkaline, alkaline earth, and transition metal salts are already known in the literature, as well as nitrogen-rich derivatives including ammonium, and the already mentioned guanidinium, aminoguanidinium, and triaminoguanidium (TAG + ) salts, , as well as several ionic liquids. Since the series of nitrogen-rich derivatives of NCA anions has not been fully investigated, we have focused on the synthesis and investigation thereof, as they tend to be promising compounds, which emerges from the structural hybridization of DCA and DN. Moreover, there are no energetic calculations or crystallographic studies on the known structures of nitrogen-rich NCA salts .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The main research on this anion, however, focused on the reaction of nitrocyanamide as a nucleophile, resulting in isocyanates, and later the implementation of the anion into transition metal complexes. These were mainly based on pyrazole and imidazole ,− ligands and were largely part of spectroscopic studies. Further energetic investigations were carried out rather recently, focusing on nitrocyanamide as part of ionic liquids used in hypergolic mixtures. In this area, the group of Shreeve has been leading the way, whereas mostly dialkylated imidazolium cations ,, or other alkylammonium salts ,− were used. However, some energetic salts, such as aminoguanidnium or triaminoguanidinium, which are solids at ambient temperature, have also been investigated …”
Section: Introductionmentioning
confidence: 99%
“…[4,5] In recent years, numerous environmentally friendly EILs based on different energetic anions [6][7][8] have displayed short ignition delay (ID) times with white fuming nitric acid (WFNA) and were expected to replace the toxic fuel such as monomethylhydrazine (MMH) [9] and unsymmetrical dimethylhydrazine (UDMH) [10,11] in liquid propellants. By appraising the properties of EILs, it is notable that energetic anions have a significant impact on their hypergolicity such as N(CN) 2 À , [12][13][14] BH 3 CN À , [15][16][17] BH 4 À , [18] and BH 3 (CN) BH 2 (CN) À . [19] To examine the impact of energetic anions on the properties of EILs, Tang et al [20] calculated the energy gap between 10 energetic anions and WFNA; then, they confirmed that the smaller the energy gap, the shorter ID times EILs have.…”
mentioning
confidence: 99%